Modelling of thermal effects in a slim tin fixed-point cell - Carvajal, Sergio A.; Ramírez, J. Herney; Bohórquez, Andrés J.; Sánchez, Ciro A.; Bohórquez Garzón, Andrés Jhovanny; Sánchez Morales, Ciro Alberto (EDP Sciences, 2019)
Slim fixed-point cells are an economic and suitable alternative for calibration of industrial platinum resistance thermometers, which are widely used in research and industrial applications. The most relevant disadvantage of slim cells is related with thermal effects produced by interactions between the cell and the furnace used for the realization of the fixed-points. This work presents the implementation of a two-dimensional numerical model that considers the transient heat transfer due to conduction, radiation and latent heat. The main goal was to evaluate different geometrical parameters in the design of slim fixed-point cells. Results show that thermal effects are mitigated when the annular distance between interior and exterior walls of the crucible is maximum, while the length of the cell and the thermo-well must be setup according to the temperature gradients in the furnace to avoid undesirable heat fluxes.